Ambiguity and Probabilistic Information - Dominiak, Adam; Lefort, Jean-Philippe (Management Science, 2021)
Experiments detecting ambiguity aversion often rely on the assumption that probabilities are exogenously given for some uncertain events. However, the canonical models that accommodate ambiguity into economic theory, such as the maxmin expected utility (MEU) and Choquet expected utility (CEU) models, are purely subjective. These models do not specify how subjects could incorporate exogenous probabilities into decisions. We study two approaches for embedding exogenous probabilities in the context of the thought experiments suggested by Mark Machina. We show that Machina’s choice behavior entails fundamentally different consequences for the ambiguity models mentioned; although it violates the CEU model, it is consistent with the MEU model. For the latter model, Machina’s experiments can test whether individuals adhere to expected utility for prospects whose consequences occur with the exogenously given probabilities. This paper was accepted by Manel Baucells, decision analysis.